Subtitling Analysis Of Directive Utterances In The Hobbit: Desolation Of Smaug Movie - Dias Damayanti, Yuli, Dr. Dwi Haryanti, M.Hum, Drs. Sigit Haryanto, M. Hum (2015)
The research paper studies about directive utterance in subtitling The Hobbit: Desolation of Smaug movie. The study aims at classifying linguistic forms and function of directive utterances and their subtitling and to describing the readability of the Indonesian subtitling of The Hobbit: Desolation of Smaug. The data of this descriptive qualitative research are directive utterance found in The Hobbit: Desolation of Smaug and its subtitling and the informants or three raters. The researcher uses documentation, questionnaire and interview the three raters to collecting the data. The researcher uses comparing method to analyze the data. The result of the research shows that; there are 14 types of linguistic form and the type of its translation in the form of directive utterance. They are: noun phrase into noun, declarative simple sentence into declarative simple sentence, declarative compound sentence into declarative compound sentence, declarative compound sentence into declarative simple sentence, declarative complex sentence into declarative complex sentence, and etc. There are 6 functions of utterance from SL to TL and there are 2 function of utterance that different from SL to TL. Moreover, the readability of subtitling is divided into three levels. Namely; high readability, medium readability and low readability. From 348 data, 339 data or 97,4% belong to high readability, 8 data or 2,3% belong to medium readability, 1 data or 0,3% belong to low readability. From the percentage, it can be concluded that directive utterance in The Hobbit: Desolation of Smaug movie is readable.